HOSPITALITY INDUSTRY AS A CATALYST FOR CULTURAL TOURISM IN KUMASI, GHANA: TEXTILE INTERIOR DECORATION WITH ADINKRA SYMBOLS - Bour-Peprah, Nancy; Kwabena Danso, Daniel; Adom, Dickson; Aboagyewaa-Ntiri, Josephine (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The hospitality industry is one of the fastest-growing industries compared to the other sectors of the global economy and it has become a competitive environment and drives the search for new ways and elements of efficient performance. Interior decoration deals with decorating a commercial business accord or a residential home to a customer's personal preferences and styles. Clients of hotels and guest houses choose to lodge at places where they consider interior designs with cultural interpretations. Adinkra symbols have distinct meanings for supporting and transmitting a complex nuanced body of practices and belief systems. A studio-based practice research method under the qualitative research approach was employed for this study to observe how hotel rooms were decorated in twenty-five (25) selected hotels in the Kumasi Metropolis, Ashanti Region, Ghana. The study found that a large number of hotels purchase foreign fabrics and already made artefacts to decorate their hotel interiors. The few hotels interior decorators who decorate their hotels with Adinkra symbols just use them with little or no consideration of their meanings. Six (6) products were produced by the researchers which were exhibited and used for the interior decoration of a hotel room. The study contends that hospitality industries in Kumasi must tactfully use cultural symbols in their interior decorations to boost their patronage.